Chemical and Radioactivity Effects of Geothermal Springs on Environmental Pollution in Seferihisar Region in Western Turkey - BOLCA, MUSTAFA; SAC, M.MURAT; ALTINBAS, UNAL; CAMGOZ, BERKAY (Asian Journal of Chemistry, 2010)
In this study, the toxic properties of Seferihisar geothermal springs are analyzed and the results show the negative effects on groups in the organisms environment or have a pollutative effect on the ecosystem. Some properties of Seferihisar region geothermal springs are determined as: temperature 69-67ºC, electrical conductivity (E.C.) 11200-22500 μmhos/cm, total cations 139.90-223.15 me L-1, total anions 134.95-220.10 me L-1, organic matter 3.30-8.10 me O2 L-1, NH4––N 2.10-2.22 me L-1, NO3––N 1.10-1.65 me L-1, NO2––N 0.44-0.95 me L-1, boron 11.00-16.60 me L-1, COD 40-122 me L-1, Fe 0.26-0.42 me L-1, Cu 0.06-0.22 me L-1, Pb 0.48-0.64 me L-1, Zn 0.06-0.13 me L-1, Cd 0.040-0.090 me L-1, Cr 0.04-0.13 me L-1, Co 0.09-0.18 me L-1, Si 33.60-71.30 me L-1, 222Rn 13.79-229.89 pCi L-1 and 226Ra 2.1-24.52 pCi L-1.